2019
DOI: 10.5888/pcd16.190065
|View full text |Cite
|
Sign up to set email alerts
|

A Public Health Framework to Improve Population Health Through Health Care and Community Clinical Linkages: The ASTHO/CDC Heart Disease and Stroke Prevention Learning Collaborative

Abstract: Thirty-one state and territorial public health agencies participated in a learning collaborative to improve diagnosis and management of hypertension in clinical and community settings. These health agencies implemented public health and clinical interventions in medical settings and health organizations using a logic model and rapid quality improvement process focused on a framework of 4 systems-change levers: 1) data-driven action, 2) clinical practice standardization, 3) clinical–community linkages, and 4) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It may have been that in some cases all LHS features were included in the actual implementation of the program, but that these components were not explicitly described in the references. The focus of LHSs for stroke ranged from targeting prevention, 16,18–20 acute treatment of ischemic stroke, 17,21 TIA, 18,22 oral care to prevention of complications after intracerebral hemorrhage, 23 and systems-level adoption to improve the whole patient journey from symptom onset to life back in the community. 15,24,25 Overall, we found more publications from high-income than low-to-middle income countries.…”
Section: Resultsmentioning
confidence: 99%
“…It may have been that in some cases all LHS features were included in the actual implementation of the program, but that these components were not explicitly described in the references. The focus of LHSs for stroke ranged from targeting prevention, 16,18–20 acute treatment of ischemic stroke, 17,21 TIA, 18,22 oral care to prevention of complications after intracerebral hemorrhage, 23 and systems-level adoption to improve the whole patient journey from symptom onset to life back in the community. 15,24,25 Overall, we found more publications from high-income than low-to-middle income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Linabarger et al report on the design and evaluation of projects in 6 state health departments to strengthen collaboration between state oral health and chronic disease programs, focusing on common risk factors. The article highlights barriers to and facilitators of implementation and provides a framework and ideas for collaboration topics that can be used by other health agencies (18). In their Program Evaluation Brief, Felipe et al describe and provide lessons learned from a learning collaborative that engaged 31 state and territorial health agencies to improve hypertension diagnosis and management, incorporating a systems-change approach and rapid quality improvement processes (19).…”
Section: Intervention Programs and Toolsmentioning
confidence: 99%
“…The Hearts of Sonoma County program (5) found that the key elements were starting small, building trust, having a framework, and providing long-term backbone support. The larger Heart Disease and Stroke Prevention Learning Collaborative, a cooperative agreement between the Association of State and Territorial Health Officials and the Centers for Disease Control and Prevention (CDC) (9), used a systems change framework, teams, and expanded self-management options and found them effective, including in rural settings. CDC supported state collaboratives with child care resource and referral networks in 10 states (10), tested methods of supporting adoption of best practices, and found improvements overall, suggesting that it may be the partnerships themselves, in addition to the programs, that make a difference.…”
mentioning
confidence: 99%